Tanggung Jawab Perusahaan Angkutan Udara terhadap Keterlambatan dan Pembatalan Penerbangan : (Studi Kasus pada Maskapai Super Air Jet) - Andin Egi Lestari; Amelia Puspa Tamara (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2025)
Passengers or users of air transportation services are increasingly experiencing flight delays and cancellations. Where the Super Air Jet airline experienced damage resulting in flight cancellations, which resulted in passengers experiencing losses in terms of both material and time. This study aims to determine how air transportation is responsible for flight delays and cancellations at the airport. This study uses a qualitative method, where this study is descriptive. Data collection in this study was through interviews, observations and documentations in the field. The results of this study indicate that air transportation is required to provide passengers with rights, namely compensation in accordance with applicable provisions in the form of food and drinks and Rp. 300.000,00 (three hundred thounsand rupiah). However,in practice passenger rights are not in accordance with receiving compensation provided by the airline. This study concludes that there must be supervision, law enforcement and firmness so that passenger rights can be protected and receive optimal justice in the world of aviation.